Metropolitan Dosoftei of Suceava (1624–1693) and the Polish–Lithuanian Commonwealth - Cojocaru , Tatiana (Balcanica Posnaniensia. Acta et studia, 2003)
Metropolitan Dosoftei (1624–1693) is one of the most prominent figures in the history of Romanian religious and literary culture. A clergyman, translator and poet, he promoted Romanian as the language of liturgy and literature, replacing the previous Old Church Slavonic. His work, highly regarded in philological studies, still requires in-depth discussion in a historical and political context, especially in relation to the Polish-Lithuanian Commonwealth. The aim of this article is to present the Metropolitan's relations with Poland and his involvement in political activities allied with the Polish raison d'état, especially during the wars with the Ottoman Empire. The work is based on an analysis of historical sources – memoirs, correspondence, church and state documents from the 17th century – as well as on a comparison of the accounts of Polish and Romanian witnesses to the events. Research shows that Dosoftei was an active participant in anti-Turkish politics and an ally of the pro-Polish faction in Moldavia. He accompanied the hospodar Petryczyce in his escape to Poland, supported John III Sobieski in the Moldavian campaign, and during his exile was intensely involved in publishing and translation. His fate in Poland – from influential refugee to respected clergyman – has been controversial in both Romanian and Polish historiography.